Valuation of Bamboo Along Pampanga Riverbank in San Simon - Nucum, Manuel U. (Future Science / FSH-PH Publications, 2024)
The Barangay San Pedro in San Simon, Pampanga, partially bounded by the Pampanga River, faces seasonal flooding due to river inundation and soil erosion. Bamboo, with its ecological and economic benefits, plays a crucial role in mitigating adverse weather effects. Studying bamboo and documenting residents’ valuation of this plant can inform intelligent responses to annual riverside community challenges. The mixed-methods research aims to create an action plan for implementing a bamboo planting program to address these issues. A field study shown that the Barangay San Pedro, situated along the Pampanga River, already boasts diverse bamboo species. Six bamboo species were mapped and identified: bayog, Buddha belly, kawayan dilaw, kawayan tinik, kawayan tsina, and Taiwan bamboo. A survey of 310 adults residing near the riverbank revealed that despite difficulties in identifying bamboo names, they were aware of its ecological significance, characteristics, and uses. On average, riverside residents expressed moderate interest in learning about bamboo cultivation and using it for livelihood. Interviews with 21 residents further highlighted their deep appreciation for bamboo. The barangay community leader even acknowledged previous bamboo initiatives but highlighted deficiencies in the existing broad action plan. The study’s proposed action plan rectifies these gaps and ensures effective implementation of the bamboo planting program. Riverside residents of the barangay recognize the value of bamboo but lack comprehensive knowledge about its diversity. The study recommends targeted information campaigns, prioritizing native bamboo like kawayan tinik, and integrating bamboo planting into the basic education curriculum and community greening efforts through multisectoral collaboration.